Angiographic profile in diabetic and non-diabetic patients with coronary artery disease in the Cardiac Specialty Hospital – Cardiac Center, Erbil, Iraq - Albarzani, Mudhafar Abdulrahman (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: The Helicobacter pylori infections role in etiology of peptic ulcer is well known, but its role in gastroesophageal reflux disease is one of the important issues which has to be confirmed. We tried to find out the effect of Helicobacter pylori infection on gastroesophageal reflux disease. Methods: The current study was done on 100 patients with gastroesophageal reflux disease from January 1st to June 30th, 2014 in Rizgary Teaching Hospital, Erbil city. The diagnosis was made by history, clinical examination, and endoscopy. Helicobacter pylori infection was confirmed by gastric biopsy and histopathological examination. We tried to find out the effects of Helicobacter pylori infection in gastroesophageal reflux disease patients and its eradication on their symptoms. The data was analyzed with the statistical package for the social sciences (version 18). Results: The mean age ± SD of participants was 37.13 ± 12.5 (17-75 years). The prevalence of Helicobacter pylori infection was 75%. The endoscopy showed that 50 out of 75 patients had erosive esophagitis and 25 out of 75 patients had normal appearance known as non-erosive esophagitis. The study showed no significance of its eradication on symptoms of gastroesophageal reflux disease. Conclusion: The effect of Helicobacter pylori infection in gastroesophageal reflux disease patients was significant regarding endoscopic finding while inversely related to symptoms severity. The eradication of infection did not cause improvement in symptom severity i.e. triple therapy not advised in the course of treatment.